Development of Immersive Augmented Reality Learning Media Integrated with Ethnoscience: A Design-Based Research Approach - Andri Imam Subekhi; Nandang Kusmana; Bagus Ardi Saputro; Yusup Junaedi; Teguh Ardianto (Journal of Educational Technology and Learning Creativity, 2026)
Purpose of the study: This study aimed to develop, validate, and evaluate an Augmented Reality (AR)-based e-module integrated with Madurese bull-racing ethnoscience (SMART) to enhance junior high school students’ numeracy skills and scientific literacy through contextualized and meaningful science learning experiences. Methodology: This study employed a Design-Based Research (DBR) approach based on the Reeves model, combined with a quasi-experimental pretest–posttest control group design. The participants consisted of 64 eighth-grade students from junior high schools in East Java, Indonesia. Data were collected through expert validation sheets, Likert-scale questionnaires, classroom observations, and achievement tests. The data were analyzed using Aiken’s V, normalized gain (N-gain), ANCOVA, and Cohen’s d effect size analysis. Main Findings: The SMART e-module demonstrated high validity (Aiken’s V = 0.87) and excellent practicality (88.6%). The experimental group showed greater improvements in numeracy and scientific literacy than the control group, with N-gain scores ranging from 0.65 to 0.72, indicating moderate-to-high learning gains. ANCOVA results revealed a significant effect of the intervention on students’ learning outcomes (F(1,61) = 18.74, p < 0.001, η² = 0.23). In addition, students exhibited consistently high levels of behavioral, emotional, and cognitive engagement throughout the learning process. Novelty/Originality of this study: This study presents an innovative integration of Augmented Reality technology and Madurese ethnoscience within a Design-Based Research framework to support contextual science learning. The study contributes to the existing literature by demonstrating that culturally responsive AR-based learning materials can effectively foster conceptual understanding, scientific reasoning, numeracy proficiency, and higher-order thinking skills simultaneously.